ADVERSE EFFECTS OF CHEMOTHERAPY ON KIDNEYS IN ONCOLOGICAL DISEASES. (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
Today, the chemotherapy method has been developed as an effective method for oncological diseases, and after the treatment, it has a negative effect on the kidneys in the body.